Predpisovanje zdravil za srčnožilne bolezni v Sloveniji - Fürst, Jurij (Farmacevtski vestnik, 2013)
The consumption of prescription drugs in Slovenia is presented, focused on cardiovascular drugs (ATC group C) and antithrombotic drugs (ATC group B01). Analysed is the use in 2012 and important changes in the period 2003-2012.
Keywords: bolezni srca in ožilja; drug; farmakoepidemiologija; poraba zdravil; predpisovanje zdravil; Slovenia; Slovenija; zdravila